2015
DOI: 10.1021/acs.jmedchem.5b00861
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Near-Infrared Fluorophores for in Vivo Detection of Amyloid-β Plaques in Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is pathologically characterized by the accumulation of β-amyloid (Aβ) deposits in the parenchymal and cortical brain. In this work, we designed, synthesized, and evaluated a series of near-infrared (NIR) probes with electron donor-acceptor end groups interacting through a π-conjugated system for the detection of Aβ deposits in the brain. Among these probes, 3b and 3c had excellent fluorescent properties (emission maxima > 650 nm and high quantum yields) and displayed high sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
152
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(168 citation statements)
references
References 55 publications
15
152
0
1
Order By: Relevance
“…3a, b, d, e and Fig. 4a, c, autoradiographic images of [ 18 F]5a and [ 18 F]9a (K i ¼ 25.7 and 21.0 nM, respectively) showed clusters of hot spots on the cerebral cortex sections of the AD patients (n ¼ 2) and Tg mouse brains, which was highly consistent with the fluorescent specks stained with DANIR 3b, a fluorescent probe targeting Ab plaques [19]. Moreover, low radioactivity accumulation was observed in white matter.…”
Section: In Vitro Autoradiographysupporting
confidence: 71%
“…3a, b, d, e and Fig. 4a, c, autoradiographic images of [ 18 F]5a and [ 18 F]9a (K i ¼ 25.7 and 21.0 nM, respectively) showed clusters of hot spots on the cerebral cortex sections of the AD patients (n ¼ 2) and Tg mouse brains, which was highly consistent with the fluorescent specks stained with DANIR 3b, a fluorescent probe targeting Ab plaques [19]. Moreover, low radioactivity accumulation was observed in white matter.…”
Section: In Vitro Autoradiographysupporting
confidence: 71%
“…Based on nanomedicine, small molecules – necessary to overcome prerequisite to cross the brain blood barrier – have been developed to label and simultaneously inhibit oligomerization of Aβ peptides. 125 The term theranostic has thus been coined to characterize these new inhibitor-biomarkers, many based on scaffolds of fluorescent probes such as ThT, to detect fibril formation in vivo and alter their accumulation. 126 These new strategies have been made possible by improved understanding of the assembly mechanism of Aβ at the molecular level, which will continue to guide rational drug design against AD.…”
Section: Aβ Tau and Alzheimer’s Diseasementioning
confidence: 99%
“…Fu et al, have explored various donor-acceptor near infrared (DANIR) probes based on different electron donor-acceptor end groups capable to interact through a π-conjugated system to detect β-A deposition in AD brain (Fu et al 2015). Authors synthesized 2 probes of different chain length and excellent fluorescent properties (emission maxima > 650 nm and high quantum yields) which were capable to penetrate BBB and also wash out from brain.…”
Section: State-of-the-art Of β-A Detectionmentioning
confidence: 99%
“…These probes exhibited high sensitivity, and high affinities to β-A aggregates (Kd = 8.8 nM and Kd = 1.9 nM). The results of in-vivo NIR imaging based on MRI showed that an optimized NIR probe can differentiate mouse model and can be used as a potential β-A neuroimaging probe for sensing β-A aggregation or plaques (Fu et al 2015) [Fig. 4B].…”
Section: State-of-the-art Of β-A Detectionmentioning
confidence: 99%
See 1 more Smart Citation